(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: This paper discusses tourists’ attitudes towards sustainable marketing factors in the context of cultural tourism. It aims to examine the influence of tourists’ attitudes on satisfaction with the overall cultural experience and perceived ecological, social, and economic effects and their impact on satisfaction. Methodology: The survey was conducted in Croatia in 2020 on a sample of 205 domestic tourists. Based on previous research, two sets of marketing items were defined: items closely related to sustainability (CRS) and items not closely related to sustainability (NCRS). Exploratory factor analysis (EFA) was applied to extract factors, followed by Principal Component Analysis (PCA). Multiple linear regression analysis was used to test the factors’ impact on satisfaction and perceived cultural tourism effects. Results: The results of factor analysis generated two CRS factors (Sustainable destination policies, Propensity for sustainable behaviour) and two NCRS factors (Respect for cultural heritage, Servicescape). The two CRS factors and the factor Respect for cultural heritage have a statistically significant influence on overall satisfaction. Moreover, the results imply that Propensity for sustainable behaviour and Respect for cultural heritage positively contribute to overall satisfaction. Among all the observed factors, only Sustainable destination policy does not significantly influence any perceived cultural tourism effects. In contrast, the perceived socio-cultural and economic effects have a positive influence on tourist satisfaction. Conclusion: The research results underpin the influence of sustainable marketing factors on satisfaction with the overall cultural experience and perceived tourism effects and their impact on satisfaction. The findings provide new insights into marketing theory and guidelines for marketing managers regarding sustainability in cultural tourism.